Pengembangan Aplikasi Bahan Ajar Kalkulus Berbasis Android - Perani Rosyani; Devi Yunita (Teknik Informatika Universitas Pamulang, 2018)
Teaching materials are the most important part of learning activities. The presence of instructional materials makes it easy for lecturers and students to give lectures and exercises in lectures especially for calculus courses. Calculus is a branch of mathematics which contains derivatives, integrals, limits, and infinite series. Calculus plays an important role in the fields of science, engineering, and economics. But some students are many who don't like the subject. Because the pattern of giving material from lecturers is less effective so students cannot develop calculus in their daily lives, especially in the field of technology. The purpose of this paper is to develop instructional material media that were previously traditional in the form of paper media and developed into an android based so that students can learn anywhere and anytime by assisting from smartphone phones. So, students can have interest and can develop theories that are in calculus in everyday life, especially in the field of technology